Components of the full blood count as risk factors for colorectal cancer detection: a systematic review protocol - Virdee, P; Kirtley, S; Elhussein, L; Watkinson, P; Holt, T; Birks, J (BMJ Publishing, 2019)
Introduction: Colorectal cancer is the fourth most common type of cancer and second most common cause of cancer-related death in the UK. The full blood count (FBC) is a blood test that may play a role in early detection of the disease. Previous studies have aimed to identify how levels of individual components, such as haemoglobin, can be used to assist diagnosis. We aim to systematically review studies to identify whether components of the FBC are risk factors for diagnosis of colorectal cancer, critically appraise the methods used to assess the association, and assess performance of components. Methods and analysis: The MEDLINE (via OVID), EMBASE (via OVID), CINAHL (via EBSCOhost), and Web of Science databases will be searched to identify in-human studies reporting the association between levels of at least one FBC component and risk of a future diagnosis of colorectal cancer. Clincialtrials.gov and the World Health Organisation (WHO) registry will be searched to identify relevant on-going research. Search terms will include relevant Medical Subject Headings (MeSH) and Emtree headings and free-text terms relating to the FBC, colorectal cancer, and diagnosis. No date or language restrictions will be applied. Two reviewers will independently identify studies for inclusion and perform data extraction. Time intervals between the blood tests and diagnosis will form subgroups for analysis. Ethics and dissemination: There is no direct patient involvement and only published articles will be reviewed; no ethical approval is required. Results from this review will set a foundation for intended future work on developing a new risk score for early detection of colorectal cancer, derived using FBC data. This systematic review will also provide guidance on the analysis of time to diagnosis. The model will be freely available to UK primary care practices.